ANALYZING IMPACT OF FAMILY ENVIRONENT ON STUDENTS - Das, Dola; Kashyap, Babhuti (International Journal of Psychosocial Rehabilitation, 2020)
Students’ academic performance and adjustment difficulties among first-year students at a health technology school are evaluated in this study. The 168 participants in the research ranged in age from 16 to 20 years old and came from four different school districts. It was an all-female group, with just 77 men in attendance. There is no difference in school adjustment or academic accomplishment between male and female students, and this holds true for students’ academic performance as well. School performance suffers as a result of difficulties at home. Studies have examined the connection between kids’ home environments and their academic achievement in secondary school. Students’ academic achievement and family relationships were examined to see how they interacted. The study’s participants were all students in high school. A variety of statistical methods were used to analyse the acquired data. Many respondents said that they lacked dedicated study spaces in their houses and had little opportunities for social connection with family and friends when it came to issues of their living quarters, but the majority of them said they were happy with their living arrangements.